Impact of Graphene Oxide Concentration and Anthocyanin Dye on the Structural, Morphological and Optical Properties of GO:TiO2 Thin Films - AlSultani, M. J.; Alias, M. F. A. (Iraqi Journal of Science, 2025)
The aim of this research is to create thin films of GO:TiO2 by the spray pyrolysis method. Hummer’s method was utilized to prepare graphene oxide (GO). Different GO concentrations of (1, 2, 3, and 4) % were used, while a TiO2 concentration was maintained at 4% to form films having various volume ratios of (1:4, 2:4, 3:4, and 4:4), which were then coated on FTO substrate at 400°C and later dipped into the pigment solution of anthocyanin (AD) obtained from red cabbage plant. Thin films’ composition, structure, morphology and optical properties were studied through energy dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), Fourier transform infrared (FTIR) microscopy, field emission scanning electron microscopy (FESEM) and UV-Vis spectrophotometry among other analytical techniques. The sizes of the crystals in these films were range from 15.6 nm to 19.38 nm and were characterized by polycrystalline structures with anatase phase. The FTIR spectra showed a functional group of all materials used in the range between 400 cm-1 and up to 4000 cm-1. The surface morphology for GO:TiO2 films showed randomly distributed aggregates or lumps of GO on the top surface of those films. As the GO concentration increased, a continuous network with TiO2 was formed. The optical properties and optical constants of the prepared GO:TiO2 and GO:TiO2:AD thin films in the spectral range 300–1100 nm were examined. The absorbance increased, the direct energy gap decreased (its value is within 3.56–3.17 eV), and the optical conductivity increased with increasing the graphene oxide concentration. The energy gap values of GO:TiO2:AD thin films, were less than that for GO:TiO2. The results showed the presence of two energy gaps within the ultraviolet spectrum (3.31-3.12) eV and visible light ranges (2.32-2.14) eV. These results are good candidates for optoelectronic devices such as hybrid or dye-sensitized solar cells and photodetectors.